An Event-Related Brain Potential (ERP) Study of Complex Anaphora in Spanish - García-Sierra, Adrián; Silva-Pereyra, Juan; Alatorre-Cruz, Graciela Catalina; Wig, Noelle (Frontiers in Psychology, 2021)
This study examines the event- related brain potential (ERP) of 25 Mexican monolingual Spanish-speakers when reading Spanish sentences with single entity anaphora or complex anaphora. Complex anaphora is an expression that refer to propositions, states, facts or events while, a single entity anaphora is an expression that refers back to a concrete object. Here we compare the cognitive cost in processing a single entity anaphora (ésta feminine; La renuncia [resignation) from a complex anaphora (esto neuter; La renuncia fue aceptada [The resignation was accepted]). Ésta elicited a larger positive peak at 200 ms, and esto elicited a larger frontal negativity around 400 ms. The positivity resembles the P200 component, and its amplitude is thought to represent an interaction between predictive qualities in sentence processing (i.e., graphical similarity & frequency of occurrence). Unlike parietal negativities (typical N400), frontal negativities are thought to represent the ease by which pronouns are linked with its antecedent, and how easy the information is recovered from short-term memory. Thus, the complex anaphora recruited more cognitive resources than the single entity anaphora. We also included an ungrammatical control sentence (éste masculine ; La renuncia [resignation]) to better understand the unique processes behind complex anaphoric resolution, as opposed to just general difficulty in sentence processing. In this case, ERPs elicited by éste masculine and ésta feminine were compared. Again, ésta elicited a larger P200. However, different from the experimental condition, a LAN effect was observed for éste; the ungrammatical condition. Altogether, the present research provides electrophysiological evidence indicating that demonstrative pronouns with different morphosyntactic features (i.e., gender) and discourse parameters (i.e., single entity or complex referent) interact during the first stage of anaphoric processing of anaphora. This stage initiated as early as 200 milliseconds after the pronoun onset and probably ends around 400 ms.